Teacher’s Use of Technology as Instructional Media - Emma Pakpahan (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
One of the key elements in advancing the teaching and learning process in a classroom is technology. It can assist the instructor in giving the class a better lesson. Technology plays a vital role in education since it allows teachers to access some amterials including playing videos, songs, movies, and even theatrical productions. It was found that a large number of teachers did not use technology in teaching. The objective of the study media was to investigate the teacher’s use of technology as instructional media. Interviews and classroom observation were used to collect the data. The participants were 11 teachers from one private school in North Sumatra. It was found that almost five teachers did not use technology in teaching.  The platform that they used mostly were Canva, PowerPoint, quizzes, and YouTube,  The reasons were the lack of facilities and the inability to use technology.